The effectiveness of health education through marga partamiangan in preventing stunting in the 1000 HPK period - Julietta Hutabarat; Maida Pardosi; elisabeth surbakti; Efendi Sianturi (MEDIA ILMU KESEHATAN, 2025)
Background: In Indonesia, stunting is still a major public health concern, especially during the First 1000 Days of Life (HPK). Prevention efforts require a contextual and culturally based educational approach. One potential forum is Partamiangan Marga, a regular family gathering that can serve as a medium for health education. Objective: This study aims to evaluate the effectiveness of health education through Partamiangan Marga in improving community knowledge and attitudes towards stunting prevention during the 1000 HPK period. Method: This research employed a pre-experimental design with a one-group pre-test and post-test methodology. The research participants consisted of 35 members of Partamiangan Marga who engaged in health counseling. The research tool utilized was a standardized questionnaire designed to assess knowledge and attitudes prior to and during the intervention. Data were evaluated utilizing a paired t-test with a significance threshold of 0.05.Results: The average knowledge score increased from 46.29 ± 12.208 to 85.29 ± 5.934, while attitudes increased from 45.20 ± 12.283 to 83.74 ± 3.592. The results of the statistical tests showed a significant difference between the pre-test and post-test, with a p-value of 0.001. Conclusion: Health education through Partamiangan Marga has been proven effective in improving community knowledge and attitudes towards preventing stunting during the 1000 HPK.